Analysis of Indonesian Export-Import Trade Contaction to Destination Countries - Indria Mayesti; Abd Halimm; Ardi Afrizal (J-MAS (Jurnal Manajemen dan Sains), 2021)
The objective of this research is to model the growth and contraction in Indonesia's export-import trade against destination countries, where for countries like China are in an average import contraction of $5,649.13 or 0.26%. Then for Japan, with an average export contraction of $8,387.62 or a growth of 5.31%. Furthermore, for Malaysia, where the import contraction amounted to $6,391.08 or with an average contraction of $291.51. Then for Singapore it experienced a contraction of imports of $3,489.52 with an average contraction of 8.69%. Furthermore, for the condition of Indonesia's export-import against Thailand, where there was an import contraction of $2,173.41 or an average contraction of 26.17%. Meanwhile, Indonesia's export-import conditions against India with an export contraction of $5,195.32 or an average contraction of 15.96%. Furthermore, the export-import condition of Indonesia against the US with a contraction value of exports was $6,355.70 or an average contraction of 6.15%.